Identification of MsCYP79 and MsCYP83 gene families and its response to mechanical damage in Medicago sativa L. - Fang Wu; Jing Zhang; Hongshan Yang; Huirong Duan (PLoS ONE, 2025)
Glucosinolate are one of the vital secondary metabolites in alfalfa (Medicago sativa L.), and primarily present as β-D-glucosinolate derivatives, improving the resistance in response to biotic and abiotic stresses of alfalfa. CYP79 (Cytochrome P450 monooxygenases) and CYP83 gene families play an important role in the core structure biosynthesis of glucosinolate. Nevertheless, a comprehensive exploration of CYP79 and CYP83 family members in alfalfa has thus far not been study. The types of glucosinolate in alfalfa were qualitative and quantitative analysis by UPLC-MS/MS. Then, we identified MsCYP79 and MsCYP83 gene families in alfalfa, and scrutinized the physicochemical attributes, gene architecture, collinearity, evolutionary trajectories, as well as expression patterns under mechanical damage. The findings revealed the glucosinolate metabolites of alfalfa divided into three classes, including 27 aliphatic glucosinolates, 9 aromatic glucosinolates, and 5 indole glucosinolates. In addition, 59 MsCYP79 family members and 56 MsCYP83 family members were identified in alfalfa, which were classified into eight main groups based on phylogenetic analysis. MsCYP79 and MsCYP83 were distributed unevenly on 26 chromosomes and had 2–6 exons. Then, employing MEME software unveiled 15 conserved motifs within the protein structures of MsCYP79 and MsCYP83. Real-time quantitative PCR was used to detect the expression level of MsCYP79 and MsCYP83 genes and demonstrated that the selected genes in alfalfa were tissue-specific and had different expression patterns in response to mechanical damage. This investigation laid a robust groundwork for substantiating the functions of MsCYP79 and MsCYP83 and facilitating the cultivation of alfalfa varieties enriched in glucosinolate content.